Acyclovir desensitization. A case report and a review of desensitization strategies - Spataro, Federico; Ria, Roberto; Choul, Nada; Vacca, Angelo; Solimando, Antonio G; Di Girolamo, Attilio (The Journal of Infection in Developing Countries, 2025)
Introduction: Acyclovir is a synthetic purine nucleoside analog that is used to treat infections caused by herpes simplex virus (HSV) and varicella zoster virus (VZV) by targeting the viral enzyme thymidine kinase. However, its use can lead to hypersensitivity reactions (HR) in rare cases, resulting in treatment discontinuation. Rapid drug desensitization (DD) by intravenous or oral administration protocols are used in these patients in order to avoid treatment discontinuation. This approach has been proven to be effective and safe. Here, we review all the desensitization strategies adopted so far, and also report our experience. Methodology: We reviewed all reports related to acyclovir desensitization; focusing on skin test results, protocols and premedication performed, and their effectiveness. We also report on the case of a 74-year-old woman affected by multiple myeloma who developed HR to acyclovir. She underwent skin tests, and lymphocyte proliferation test (LPT) with acyclovir, and was subsequently subjected to oral desensitization. Results. Six articles met the inclusion criteria and were analyzed in this review, along with a case report. All DD procedures were well-tolerated, with only mild reactions reported in one patient. Skin tests gave negative results but one result was deemed doubtful response. Moreover, the LPT performed in our case had positive result, indicating a hypersensitive immune response to acyclovir. Conclusions. Acyclovir desensitization is a safe and effective approach for patients experiencing HR. Standardized in vivo and in vitro testing are required to better estimate the risk of DD and find the safest individualized DD protocol.